Feasibility and acceptability of integrating mass distribution of azithromycin to children 1-11 months into a trachoma mass drug administration campaign to reduce child mortality in Côte d'Ivoire. - Lisa Dulli; Fatoumata Touré; Adam Djima Mama; Emily Evens; Kate Murray; Norbert N'goran Djè; Stéphane Koné; Pat Sadate-Ngatchou; Anoma Bovary; Marga Eichleay; Milenka Jean-Baptiste; Aboulaye Méité (Public Library of Science (PLoS), 2024)
Evidence suggests that bi-annual mass drug administration (MDA) of single-dose azithromycin to 1-11 month-old children reduces child mortality in high child-mortality settings. Several countries conduct annual MDAs to distribute azithromycin to individuals ages 6 months and older to prevent trachoma infection. This study examined the feasibility and acceptability of reaching 1-11 months-old children during a trachoma MDA in Côte d'Ivoire by extending azithromycin distribution to infants 1-5 months old during the campaign. In November 2020, the study piloted single-dose azithromycin for 1-5 month-olds during a trachoma MDA in one health district. Monitoring data included the number of children reached and occurrences of adverse drug reactions. Feasibility, the extent to which the target population received the intervention (coverage), was assessed through a population-based, household survey with parents/caregivers of eligible children conducted after the MDA. Acceptability was explored through in-depth interviews (IDIs) with parents/caregivers of eligible children, focus group discussions (FGDs) with community drug distributors (CDDs), and IDIs with their supervisors. CDD FGDs and supervisor IDIs also documented implementation challenges and recommendations for scale-up. 1,735 1-5 month-olds received azithromycin during the pilot activity (estimated population coverage of 90.2%). Adverse drug reactions were reported for 1% (n = 18) infants; all were mild and self-limited. The post-MDA coverage survey interviewed 267 parents/caregivers; survey-based intervention coverage was 95.4% of 1-5 month-olds. Qualitative data revealed high intervention acceptability among parents, CDDs, and supervisors. Implementation challenges included the need to weigh babies to calculate dosage for 1-5 month-olds and the need to obtain written informed consent from parents to provide the drug to 1-5 month-olds. CDDs also indicated the need for more information on azithromycin and possible side effects during training. Delivering azithromycin to younger infants appears acceptable to parents and implementers; >90% coverage indicates feasibility to integrate into a trachoma MDA. (Clinicaltrials.gov ID number: NCT04617626).